Political and Economic Cooperation between Russia and the Slovak Republic: Possible Development Scenarios - V. A. Denisenko; N. A. Malchushkin (Управленческое консультирование, 2020)
The article is dedicated to recent domestic political transformations in Slovakia and their possible impact on Russian-Slovak relations. The paper studies the main aspects of the current political and economic partnership between the Russian Federation and the Slovak Republic; it is indicated that economic cooperation with Russia remains a relatively significant foreign policy aspect for Slovakia, primarily due to energy supplies. Nevertheless, the gradual decrease in the intensity of bilateral interaction is highlighted. According to the authors, the “anti-Russian pivot” of Slovakia in 2020 can contribute to a further reduction in the scale of Russian-Slovak cooperation; the Slovak elections radically altered the configuration of political forces within the country, the republic’s parliament is led by the opposition forces with clear anti-Russian rhetoric.Considering possible variations of Russian-Slovak political and economic cooperation in the foreseeable future, authors propose moderately optimistic, neutral and pessimistic scenarios. It is underlined that the damage from the predicted deterioration in relations for Russia due to the current trends in bilateral cooperation between the countries is assessed as rather insignificant.